Implementation of Teaching at the Right Level through Differentiated Learning on Senior High School Students’ Learning Outcomes - Saverinus Fambolan; Siprianus Suban Garak; Ahmad Jais; Muhammad Fuadi (Journal of Insan Mulia Education, 2025)
The purpose of this study was to examine the improvement of learning outcomes among Grade XI.C students of SMAN 1 Kupang through the implementation of the Teaching at the Right Level (TaRL) approach using differentiated learning. The research method employed was Classroom Action Research (CAR), conducted in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The research sample consisted of 28 students from class XI.C. The findings indicated a significant improvement in students’ learning outcomes through the application of the Teaching at the Right Level approach. This was evidenced by the substantial increase in achievement across each cycle: during the pre-cycle, 17.71% of students achieved mastery, which rose to 42.85% in Cycle I, and further increased to 85.71% in Cycle II. Therefore, the Teaching at the Right Level approach through differentiated learning was proven effective in improving students’ learning outcomes.